Legal Politics Of The Constitutional Court Decision Number 22/Puu-XV/2017 Concerning The Minimum Age Limit For Marriage - Khoirul Anwar; Dhyan Andika Irawan; Ahmad Rifai; Sofyetin Atiana (Rechtsvinding, 2026)
This research reviews 2 problem formulations, First, how is the history of the regulation of the minimum age limit for marriage before the Constitutional Court Decision No. 22 / PUU- XV / 2017? Second, how is the legal policy of the minimum age limit for marriage after the Constitutional Court Decision No. 22 / PUU- XV / 2017? To be able to review the case, this research procedure is used with a normative legal study that uses a historical approach and laws, where the data sources used are secondary information sources. Based on the research and reviews conducted, the following results were obtained: Initially, the history of setting minimum marriage age limits in Indonesia began before the Dutch colonial era. At that time, the applicable marriage law was based on each individual's religious law. Later, during the Dutch occupation, ethnicity-based classifications were implemented, with each group having its own specific rules. During the Old Order, Law No. 22 of 1946 concerning Marriage Registration, Divorce, and Reconciliation (hereinafter referred to as NTR) was enacted. During the New Order, Law No. 1 of 1974 concerning Marriage was enacted, followed by its first revision during the reform era, Law No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage. Second, the political will of the state government is a determining factor in the direction of the law, including the determination of minimum marriage age limits.